Geophysics conquering new territories: The rise of "agrogeophysics". Issue 4 (26th May 2021) - Garré, Sarah; Hyndman, David; Mary, Benjamin; Werban, Ulrike
Abstract: Agriculture is facing immense challenges. We have to produce enough food while safe‐guarding the environment for future generations. This results in the need to use less water and fertilizer, and to harness soil quality. Key to achieving this goal is improving the understanding of processes and interactions governing the soil–plant–atmosphere continuum of agricultural ecosystems. Geophysical tools have great potential to better characterize and quantify these processes noninvasively from the plot to landscape scale. Nevertheless, a number of challenges remain for geophysical results to be better exploited by different scientific communities and by decision‐makers. In this special section, we explore ongoing research in the relatively new field of agrogeophysics, and we provide an overview of potential applications and highlight future research needs. Core Ideas: Geophysical techniques are future tools for sustainable management of water and nutrients in agroecosystems. Spatial electromagnetic data help to characterize large areas and to understand underlying processes. Geophysical characterization offers insights in processes driving the soil–plant–atmosphere continuum. Geophysics to characterize root properties and processes is a growing interdisciplinary research topic.